Surgical vs. conservative treatment for hip osteoporotic fracture in maintenance hemodialysis patients: a retrospective analysis - Zhang, Man-Yu; Song, Wei; Wang, Jing-Bo; Lv, Rui-Qian; Zhao, Fu-Hao; Yang, Ding-Wei (Frontiers in Surgery, 2024)
BackgroundHSip Osteoporotic fractures are common complications with high mortality in patients undergoing maintenance hemodialysis (MHD). It remains unclear whether surgical or conservative should be adopted for hip fractures in MHD patients.MethodsA retrospective analysis was conducted in Tianjin Hospital of Tianjin University from August 2019 to August 2023. A total of 43 MHD patients with hip fracture were included, with 30 cases in the surgical group and 13 cases in the conservative group. The differences in cumulative survival rates, time to first ambulation, Harris score, Barthel index, and incidence of complications were compared.ResultsThe surgical group had remarkable lower mortality rates as compared with the conservative group at 1, 2, 3, 6, 12, 24 months (13.33 VS. 38.46%, 26.67 VS. 53.85%, 26.67 VS. 53.85%, 26.67 VS. 61.54%, 26.67 VS. 61.54%, and 26.67 VS. 69.23%). In the surgical treatment group, the first ambulation time was reduced to 28 (26) days, which was superior to the conservative group (134.17 ± 43.18 days, P < 0.001). The Harris score at 1 month (61.50 ± 4.10) and the Barthel index at 3 months (95, 11.25) were also significantly higher (P < 0.001). Furthermore, the surgical group had a significantly lower overall incidence of complications (60.00 vs. 92.31%, P = 0.034). The risk of death and complications of surgical treatment was only 23.0 and 32.4% of conservative treatment in MHD patients with hip fracture.ConclusionSurgical treatment is effective and safe and should be the first choice for hip fracture in MHD patients.